Histoarchitectonics of a thyroid gland in the conditions of a blastomogenesis. - Khripkov, I. S. (Морфологія / Morphologia / Morfologìâ, 2012)
Experiment has been supplied on 20 white rats-males in mass of 140-160 g to whom under a skin the tumoral strain of a Guerin’s carcinoma has been transplanted. The purpose of the real research was studying distant tumour influences on histotopography structural components of a thyroid gland. Distant influence of a tumour on a thyroid gland calls essential rearrangements of a stroma and a parenchima of an organ which are accompanied by depression of functional activity thyrocyties and reduction of quantity of haemocapillars of a stroma of an organ.